We need to solve the equation: w² + 36 = 12w
⇒ w² - 12w + 36 = 0
⇒ w² - 6w - 6w + 36 = 0 (Breaking 6w such that their product is 9w²)
⇒ w × (w - 6) - 6 × (w - 6) = 0 (Extracting common factors)
⇒ (w - 6) × (w - 6) = 0
⇒ (w - 6)² = 0
⇒ w = 6
Hence, the correct answer is 6 which is the fourth option from the replacement set
Answer:
Step-by-step explanation:
Next time, please be sure to share the possible answer choices. Also, please use " ^ " to indicate exponentiation: x^2 + (2/3)x.
Let's actually "complete the square" here:
Starting with x^2 + (2/3)x, identify the coefficient of the x term (it is 2/3).
Take half of that, which results in 2/6, or 1/3.
Square this result, obtaining (1/3)^2 = 1/9.
Add to, and then subtract from, this square:
x^2 + (2/3)x + 1/9 - 1/9
Rewrite x^2 + (2/3)x + 1/9 as the square of a binomial:
(x + 1/3)^2 - 1/9
In review: add 1/9 to, and then subtract 1/9 from, x^2 + (2/3)x
Answer:
Step-by-step explanation:
hello :
-2x+6y=-18
divide both sides by 2 : -x+3y = -9
3y = x-9
now divide both sides by 3
y= (1/3)x -3
$375 would be the original price if you took 20 percent of it. 20 percent of 375 is 75.. is that helpful?